2018
DOI: 10.1038/s41598-018-20170-1
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxylamine released by nitrifying microorganisms is a precursor for HONO emission from drying soils

Abstract: Nitrous acid (HONO) is an important precursor of the hydroxyl radical (OH), the atmosphere´s primary oxidant. An unknown strong daytime source of HONO is required to explain measurements in ambient air. Emissions from soils are one of the potential sources. Ammonia-oxidizing bacteria (AOB) have been identified as possible producers of these HONO soil emissions. However, the mechanisms for production and release of HONO in soils are not fully understood. In this study, we used a dynamic soil-chamber system to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 50 publications
1
42
0
Order By: Relevance
“…Furthermore, Caranto and Lancaster (22) showed that NO is a precursor to NO 2ˉi n AOB via the NH 2 OH/NO obligate intermediate mechanism, indicating a possible biogenic pathway for aerobic-derived NO. Evidence for AOB contributing to NO release comes from culture-based assays showing that AOB produces significantly more NO than AOA (14,21). However, this phenomenon has yet to be demonstrated in a soil matrix, leading to questions regarding the environmental significance of this proposed mechanism.…”
Section: Significancementioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, Caranto and Lancaster (22) showed that NO is a precursor to NO 2ˉi n AOB via the NH 2 OH/NO obligate intermediate mechanism, indicating a possible biogenic pathway for aerobic-derived NO. Evidence for AOB contributing to NO release comes from culture-based assays showing that AOB produces significantly more NO than AOA (14,21). However, this phenomenon has yet to be demonstrated in a soil matrix, leading to questions regarding the environmental significance of this proposed mechanism.…”
Section: Significancementioning
confidence: 99%
“…Most studies have implicated abiotic mechanisms associated with NO x (NO and NO 2 ) chemistry as the primary driver of HONO production. However, it has recently been suggested that a portion of the NH 2 OH produced via NH 3 oxidation is released from the soil as HONO (14,33), assuming that certain conditions associated with soil pH, water content, and surface area are met (34,35). Additionally, biologically produced NO 2ˉm ay be protonated to form HONO.…”
Section: Significancementioning
confidence: 99%
See 2 more Smart Citations
“…not only atmospheric particles but also ground soils, with the report of direct soil emission (Meusel et al, 2018;Bhattarai et al, 2018). These heterogeneous conversions and emissions from soil are controlled by several conditions such as pH, moisture, and microbials and mainly affect daytime HONO concentrations (Ermel et al, 2018;Wu et al, 2019). For these reactions, the measurement of active surface area hinders the accurate estimation of HONO formation (Romer et al, 2016).…”
Section: Introductionmentioning
confidence: 99%